توظيف النحو في إثراء الدرس التفسيري عند الإمام ابن باديس من خلال تفسيره: مجالس التذكير من كلام الحكيم الخبير" - أسامة, حراث (University of eloued جامعة الوادي, 2021)
"هذا البحث يتناول موضوعا نحويا تفسيريا، حاولت فيه -قدر الإمكان- أن أبين وجه العلاقة بين العلمين انطلاقا من تفسير ابن باديس، وكيف كان الإمام يوظف علم النحو في اقتناص المعاني التفسيرية...فكان عنوان البحث هكذا: ""توظيف النحو في إثراء الدرس التفسيري عند الإمام ابن باديس من خلال تفسيره: مجالس التذكير من كلام الحكيم الخبير"". والإشكال الذي جعلته نصب عيني طوال الدراسة هو: هل كان ابن باديس -رحمه ّاالله- يعرض المسائل النحوية عرضا جافا معزولا عن التطبيق، أم كان يوظفها في إثراء الدرس التفسيري، ويجعلها خادمة له؟ وللإجابة عن هذه الإشكالية قسمت بحثي إلى قسمين؛ قسم نظري، وقسم تطبيقي، أما القسم النظري فجعلته في مبحثين فقط، وتحت كل مبحث تمهيد ومطالب. المبحث الأول خصصته لترجمة مبتكرة عن الإمام، فذكرت أهم المحطات في حياته، ثم تناولته مفسرا، ومنه تخلّصت إلى تناوله لغويا، ومنه تدرجت للكلام عن أهم مباحث اللغة التي اشتمل عليها تفسيره. وأما المبحث الثاني فقد خصصته لإبراز العلاقة بين علم النحو والتفسير، فمهدت بذكر نبذة عن علم النحو والتفسير، ومنها تخلصت إلى العلاقة بين العلمين، فذكرت أن النحو نشأ في أحضان القر آن الكريم ولخدمته، ثم ذكرت افتقار المفسر إلى علم النحو، وحرمة تعاطي التفسير دون زاد لغوي نحوي، حتى توصلت إلى أهم النحاة الذين ألفوا في تفسير القرآن، وبه ختمت القسم النظري. وأما القسم التطبيقي من البحث فقد جعلته في أربعة مباحث، وتحت كل مبحث عدد من المطالب؛ المطلب الأول تحدثت فيه عن توظيف المعارف والنكرات في استنباط المعاني،والمطلب الثاني تحدثت فيه عن توظيف أدوات المعاني في الاستنباط، والمطلب الثالث تحدثت فيه عن توظيف التوابع في الاستنباط، والمطلب الرابع خصصته لمسائل متفرقات. و أهم النتائج التي توصلت إليها بعد هذه الرحلة الماتعة النافعة؛ رحلة الإجابة عن الإشكال: -أنه لا يمكن ألبتة الفصل بين النحو والتفسير، و ّ أن تفسير ابن باديس بالرغم من كونه تفسيرا إصلاحيا تربويا هدائيا؛ لم يخل من مسائل لغوية عموما، ومن مسائل نحوية علىوجه الخصوص وأنه لم يكن يسوق تلك المسائل النحوية سياقة جافة مملّة كما كان يفعل ، معاصروه من مشايخ الزيتونة الذين انتقد عليهم الإمام مناهجهم في التعليم، وإنما أسلوبه في عرض المسائل النحوية أسلوب انتقائي عملي؛ فهو دوما يكتفي بالمسائل التي تترتب عليها فوائد عملية استنباطية فحسب، ويعرض عن التنظيرات التي لا طائل تحتها، فلا يأتي بالنحو ُمن أجل النحو، بل يأتي بالنحو من أجل التفسير.""This research deals with an explanatory grammatical topic, in which I tried - as much as possible - to show the face of the relationship between the two sciences based on the interpretation of Ibn Badis, and how Imam used to employs grammar in eliciting explanatory meanings...The title of the paper was ""Employing Grammar to Enrich the Interpretative Lesson of the Imam Ibn Badis through His Interpretation: Councils of Reminder of the Speech of the Expert Sage"". The problem I kept in mind throughout my study was: Did Padis' reformist interpretation contain grammatical problems? If so, Was he offering her dry, isolated from the application, or was he hiring her to enrich her interpretive lesson, and making her his servant? To answer this problem, I divided my research into two parts; The theoretical section consists of only two studies, and under each preface and request. The first research I devoted to an innovative translation of the Imam, so I mentioned the most important stations in his life, then I addressed it as an interpreter, and from it I ended up dealing with it linguically, and from it I graduated to speak about the most important discussion of the language that was included in his interpretation. The second paper focused on the relationship between grammar and interpretation, starting with a brief overview of grammar and interpretation From there, I concluded the relationship between the two sciences, stating that grammar arose in the arms and service of the Holy Koran, then mentioning the interpreter's lack ofgrammar and the inviolability of interpretation without adding to the language of the Koran. The practical part of the research consists of four subjects, with each subject to a number of demands; The first is about the use of knowledge and negatives in eliciting meaning, the second is about the use of tools of meaning in eliciting, the third is about the use of satellites in eliciting, and the fourth is about miscellaneous issues. The main findings of this enjoyable journey; Problem answer journey: - It is absolutely not possible to separate between grammar and interpretation, and that Ibn Badis' interpretation, despite being a reformist, educational, guiding interpretation; It was not free from linguistic issues in general, and from issues In particular, grammatical issues, and that he was not driving those grammatical issues as tedious as his contemporaries, Zeitouna sheiks, for whom he criticized his curriculum of education, but rather his way of presenting grammatical issues in a selective and practical manner; It always only comes to questions of deductive practical benefit, displays useless theorizing, and comes not grammar for grammar, but grammar for interpretation.."
لغة دراسات
Keywords: ابن باديس، النحو، توظيف، التفسير; Ibn Badis-grammar-Recruit-Interpretation